2011
DOI: 10.1080/03630242.2011.633598
|View full text |Cite
|
Sign up to set email alerts
|

A Will Without a Way: Barriers and Facilitators to Exercise During Pregnancy of Low-Income, African American Women

Abstract: The objective of the authors in this study was to identify pregnant, low-income African American women's barriers and facilitators to exercise during pregnancy. A series of six focus groups with pregnant African American women were audio-recorded and transcribed verbatim. Focus group transcripts were qualitatively analyzed for major themes and independently coded for barriers and facilitators to exercise during pregnancy. A total of 34 pregnant, African American women participated in six focus groups from June… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
43
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(44 citation statements)
references
References 24 publications
1
43
0
Order By: Relevance
“…Group-based exercise sessions (i.e., walking, Zumba ® , cycling) represent an ideal strategy for researchers to accomplish this. Group-based exercise sessions also provide the opportunity for AA women to engage in PA with women who they perceive as similar or “like” themselves (which is an established motivator for PA among AA women; [40, 58, 104, 105]), while enhancing social support, self-efficacy, and self-regulatory skills for PA. For women who are unable to attend group-based sessions due to family, work, and/or community commitments, home-based exercise videos and/or demonstration manuals represent an ideal option, as they can provide women with experience of performing a variety of activities while allowing for flexibility of participant schedules.…”
Section: Resultsmentioning
confidence: 99%
“…Group-based exercise sessions (i.e., walking, Zumba ® , cycling) represent an ideal strategy for researchers to accomplish this. Group-based exercise sessions also provide the opportunity for AA women to engage in PA with women who they perceive as similar or “like” themselves (which is an established motivator for PA among AA women; [40, 58, 104, 105]), while enhancing social support, self-efficacy, and self-regulatory skills for PA. For women who are unable to attend group-based sessions due to family, work, and/or community commitments, home-based exercise videos and/or demonstration manuals represent an ideal option, as they can provide women with experience of performing a variety of activities while allowing for flexibility of participant schedules.…”
Section: Resultsmentioning
confidence: 99%
“…Issues surrounding information, family and work commitments, costs, social influences and understanding health information were also identified in a recent review examining barriers and facilitators to the implementation of community-based lifestyle interventions among black and minority ethnic groups in the UK . Lack of information and financial and neighbourhood resources, and group exercise and affordable and accessible facilities have been identified respectively as barriers and facilitators of physical activity among low-SES pregnant AfricanAmerican women (Krans and Chang, 2011). Another recent review found insufficient information, perceptions of control over health and concerns over personal safety to be barriers to physical activity in South Asian older adults (Horne and Tierney, 2012).…”
Section: Discussionmentioning
confidence: 97%
“…It is not surprising that financial concerns can prevent children from participating in aerobic activities, as this barrier has been identified by national studies and studies of similar neighborhoods. 29, 32,33 For example, when parents are making inexpensive child care arrangements, they are often happy to find a safe place for their children. Understandably, parents with limited options may not prioritize active play when they are balancing safety and financial concerns.…”
Section: Discussionmentioning
confidence: 99%